ANALISE FAMILIAL DO COMPORTAMENTO IN VITRO DOS MACROFAGOS HUMANOS FRENTE AO MYCOBACTERIUM LEPRAE - Freire-Malia, D. V. (My University, 1983)
The lysogenic capacity of human macrophages facing M. leprae in vitro may be dependent on an important genetic component. Although the familial aggregation of the trait is demonstrated, this is a necessary but not sufficient condition to prove genetic influence. The data do not fit some simple genetic models (autosomal dominant or incompletely dominant gene; dominant or recessive sex-linked gene). The results obtained are consistent with the hypothesis that the macrophages' lysogenic capacity is mainly due to a major gene with variable expressivity. This hypothesis may be too simple to account for the whole variability detected and therefore must be considered a working hypothesis.
Familial analysis of behavior of human macrophages towards Mycobacterium leprae in vitro
Keywords: genetics; heredity; human; leprosy; macrophage; mycobacterium leprae; blood; in vitro study; Mycobacterium leprae; phenotype; physiology; English Abstract; Human; In Vitro; Leprosy; Macrophages; Phenotype; Support, Non-U.S. Gov't